Validity of Transcutaneous Bilirubinometer in Neonates as Compared to Laboratory Serum Bilirubin Estimation - Tariq Saeed, Muhammad Zahoor ul Haq, Mohsin Butt, Tariq Mahmood Raja, Rubina Zulfiqar, (Journal of Rawalpindi Medical College, 2013)
Background : To determine the validity of transcutaneous bilirubinometer, keeping laboratory serum bilirubin level as gold standard and to compare bilirubin levels by both methods after treatment i.e. phototherapy and exchange transfusion in the evaluation of neonatal jaundice. Methods: In this cross sectional study serum samples of 122 neonates, up to 01 week of age, of either sex, having visible clinical jaundice were sent to pathology laboratory for total bilirubin estimation. At the same time, total bilirubin level was checked and recorded by a BiliCheck Jaundice Meter. Results: Before start of treatment serum bilirubin values ranged from 150-300mol with mean of 220mol while transcutaneous bilirubin values ranged from 155-320mol with mean of 229mol. The bilirubin value obtained by transcutaneous bilirubinometer does not differ significantly from laboratory serum bilirubin measurement before treatment. Conclusion: Bilicheck Transcutaneous Bilirubinometer, as a screening device, offers an accurate, rapid, economic and noninvasive means of assessing plasma bilirubin concentrations in neonates.